Desafios na inclusão de saberes e práticas socioambientais locais no Plano de Manejo da Resex marinha Caeté-Taperaçu - OLIVEIRA, Marcelo do Vale (Universidade Federal do Pará, 2021)
The general objective is to understand the challenges of including local social and environmental knowledge and practices in the co-production of the Resex Caeté-Taperaçu Management Plan. The central question is what are the challenges of including local socioenvironmental practices in the co production of the Management Plan for the Caeté-Taperaçu marine resex? From an approach of the Sociology of Public Action (LASCOUMES and LE GALÈS, 2012; TEISSERENC and TEISSERENC, 2014) we link a new perspective of interdisciplinary view on public policies, in which the State has its centrality contested, with greater participation of different actors in discussions with implementations and management, based on new dynamics and local mobilizations. The analyzed database was constituted from documentary information and interviews of twenty people involved in the co production. And the main result shows that in a process so rich in learning and socioenvironmental achievements, it has not yet been possible to break with the hegemony of other interests linked to a rationality that is neither environmental nor local populations. However, the capacity to resist, to invent, to learn, from social segments such as traditional populations, in partnership with other segments of actors (teaching and research institutions, State bodies), has been able to impose itself, face political and economic forces that deny them, through the adoption of environmental conservation references.